Pericles and the definition of democracy (Thuc. 2.37.1): Renaissance, Modern and Contemporary interpretations - Iglesias-Zoido, Juan Carlos (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2022)
The aim of this study is to review Renaissance, Modern and Contemporary interpretations of Thuc. 2.37.1, in wich Pericles offers a polemical definition of Democracy.
Keywords: Thucydides; Funeral Oration; Democracy; Scholia; Translations